NFC-Based attendance monitoring system for smart university environment - Aqqiela Zuhra Zuhedy Zay (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
The use of NFC technology is growing rapidly and implemented in various applications. It aims to reduce the steps needed to perform tasks by the user in day to day operations such as payment, electronic ticketing, attendance system, and other office related tasks. The university institution contains mainly a large population of administrative staff, faculty members and students. Each individual performs specific activities and requires the interaction of many individuals. These activities are often trivial but require exhaustive user interaction, for example, keeping track of students' assignments or checking and signing a stack of documents. This makes simple activities to be cumbersome, strenuous and time consuming for most individuals. In this study, university smart environment is implemented using NFC for attendance monitoring system. The application involves several different concerns in security, access control and managing physical and virtual components. These concerns are studied to create an easy-used attendance monitoring system using NFC enabled technology to be applied in a smart university environment. An experiment was run involving 30 participants act as students and 15 participants as lecturers. The result of the experiment shows that implementing NFC in university workflow process will significantly reduce the workload and money spent on skilled man power and resources. It also is proved to be environmental friendly.